Viscoelastic material properties determine the contact mechanics of hydrogel spheres - Shakya, Chandan; van der Gucht, Jasper; Dijksman, Joshua A. (Frontiers in Physics, 2024)
Granular materials are ubiquitous in nature and industry; their mechanical behavior has been of academic and engineering interest for centuries. One of the reasons for their rather complex mechanical behavior is that stresses exerted on a granular material propagate only through contacts between the grains. These contacts can change as the packing evolves. This makes any deformation and mechanical response from a granular packing a function of the nature of contacts between the grains and the material response of the material the grains are made of. We present a study in which we isolate the role of the grain material in the contact forces acting between two particles sliding past each other. We use hydrogel particles and find that a viscoelastic material model, in which the shear modulus decays with time, coupled with a simple Coulomb friction model captures the experimental results. The results suggest that the particle material evolution itself may play a role in the collective behavior of granular materials.